A Clinical Update on the Different Methods to Decrease the Occurrence of Missed Root Canals - Mohammadi, Zahed; Asgary, Saeed; Shalavi, Sousan; Abbott, Paul V. (Iranian Endodontic Journal, 2016)
One of the main causes of endodontic treatment failure is the clinician’s inability to localize all the root canals. Due to the complex anatomy of the root canal system, missed canals are not uncommon. There are several strategies to decrease the possibility of missed root canals starting with good pre-operative radiographies. In order to overcome the limitations of conventional radiographies, cone-beam computed tomography (CBCT) can be considered. A correct access cavity preparation is of pivotal importance in localizing the orifices of the root canals. Furthermore, ultrasonics are very important devices to find missed canals. Increasing magnification and illumination enhance the possibility of finding all root canals during root canal treatment. The purpose of the present paper was to review all of the above techniques and devices. Keywords: Access Cavity; Cone-Beam Computed Tomography; Microscope; Missed Canals; Radiography; Root Canal Morphology; Transillumination; Ultrasonic